Refining Western Dementia-Risk Paradigms: Evidence From a Decade of the Korean Longitudinal Study on Cognitive Aging and Dementia - Han, Ji Won; Oh, Dae Jong; Kim, Tae Hui; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Moon, Seok Woo; Park, Joon Hyuk; Ryu, Seung-Ho; Youn, Jong Chul; Lee, Dong Young; et al. (Journal of Korean medical science, 2025)
As the most rapidly aging nation, Korea offers a unique lens into the future of dementia, one of the most pressing global health challenges of the 21st century. The Korean Longitudinal Study on Cognitive Aging and Dementia (KLOSCAD), launched amid the country's rapid demographic transition, exemplifies how population-specific research can guide national policy and challenge universal assumptions in dementia science. More than a cohort study, KLOSCAD provides a methodological blueprint for identifying culturally relevant risk factors, testing the applicability of Western models, and shaping prevention strategies for local contexts. Its evolution from a national study to a globally recognized platform reflects the value of sustained governmental support, strategic design, and international collaboration. As the dementia epidemic's center shifts to Asia, the KLOSCAD experience underscores that diversity is not a confounder but a scientific opportunity, critical for building both universal and context-sensitive approaches to understanding and preventing dementia worldwide.